Local agenda 21 (Institution of Civil Engineers, 2000)
Local Agenda 21 puts sustainable development into practice.The name derives from the 1992 Earth Summit when national leaders agreed on a programme of action for the 21st century. Under Local Agenda 21, local authorities are asked to reach out to all sectors of their communities and help forge a consensus on the problems that need to be overcome locally to secure a more sustainable future.